Loads and effects of ship-generated, drawdown waves in confined waterways - A review of current knowledge and methods - Dempwolff, León-Carlos; Melling, Gregor; Windt, Christian; Lojek, Oliver; Martin, Tobias; Holzwarth, Ingrid; Bihs, Hans; Goseberg, Nils (Journal of Coastal and Hydraulic Structures, 2022)
A ship in motion generates a complex wave field consisting of several superimposed wave systems. The relevance of the wave systems' components varies, depending on individual ship and waterway parameters. This review work is specifically concerned with the long-period, primary wave system, large-volume ships travelling through confined waterways, generate, as it may exert intensive wave and current loading on the banks, affecting local morphology, engineering structures and ecology So far, the effect of ship-generated waves on waterway embankments has yet only routinely been considered for inland waterways with a constant cross-section. Less attention has been payed to the ship-induced wave and current loading in more complex bathymetries like coastal waterways and estuaries, as naturally occurring loads had been thought to dominate. However, the hydrodynamic loads induced by ships grow and become increasingly relevant in coastal waterways, due to continuously growing dimensions of sea-going ships. At the same time, requirements rise to allow for restoring the ecological value of of inland and coastal waterways, leading to spatially more diverse bathymetries and embankment structures. Hence, the prediction of ship-generated primary wave magnitudes at banks becomes increasingly complex, due to deformation processes of the propagating waves in shallow water. Knowledge on ship-generated waves characteristics and methods to predict induced loads are thus essential for the assessment of bank stability and the dimensioning of engineering structures to resist present-day and prospective ship-induced loads. This review paper compiles, analyzes and assesses the findings of previous research quantifying the relevance of primary waves for the surrounding waterways and shows interconnections to the questions studied within naval hydrodynamics for confined waterways. Commonly applied methods for wave prediction are reviewed, highlighting their relevance and limitations. Finally, a concept for coupled numerical model development is suggested, based on the success of different modelling approaches presented previously.